Factors affecting the spatial resilience of Ethiopia's secondary cities to urban uncertainties: A study of household perceptions of Kombolcha city - Mulugeta Maru; Hailu Worku; Joern Birkmann (Heliyon, 2021)
The resilience measurement focuses on urban shocks and stresses, which are excluded from current spatial resilience assessments. As a result, existing literature suggests that research in secondary cities of the global south is needed to understand better spatial resilience in the face of multivariate, intersecting, and uncertain challenges. This study aims to determine the factors affecting the spatial resilience of Ethiopia's secondary cities to urban uncertainties using household perceptions of Kombolcha city. The study collected empirical data through questionnaires and key informant interviews, and then analyzed those using SPSS and the Analytic Hierarchy Process. Accordingly, seventeen environmental and physical urban problems affecting the spatial resilience of the country's secondary cities were identified. Deforestation, surface flooding, landslides, poor solid waste management, and inadequate drainage facilities were perceived as top priority urban problems in Kombolcha city with the respective values of 19.73%, 13.02%, 12.70%, 7.59%, and 6.82% of the four hundred sampled households. However, water scarcity and wind-related shocks, scoring 1.48% and 1.89%, respectively, were the least recurring urban problems. The city's spatial resilience is further limited by unsustainable material and resource consumption, a lack of infrastructure, poor transportation system conditions, poor implementation of response measures: lack of appropriate planning, and non-long-lasting biophysical measures. The household perception also showed that the urban uncertainties are severe in the city, with a 49.48% response rate. The findings also revealed a relationship and commonalities amongst the problems exacerbated by land-use zoning changes and the thriving informal settlements. The study implied that improving secondary cities' coping, adaptation, and governance systems are critical for mitigating the perceived urban problems and making cities spatially resilient. Thus, the study's spatial planning implications are that local governments in secondary cities commit to localizing international initiatives, strictly establishing and enforcing local resource utilization strategies, and improving living conditions in their cities.